Clinical features of facioscapulohumeral muscular dystrophy 1 in childhood. (20th January 2019) - Steel, Dora; Main, Marion; Manzur, Adnan; Muntoni, Francesco; Munot, Pinki
Abstract : Aim: To explore the clinical course of patients presenting with facioscapulohumeral dystrophy type 1 (FSHD1) in childhood, with a view to identifying areas where they differed from older patients and where extra support or monitoring might be required. Method: A retrospective case‐notes review of children with FSHD1 seen at a tertiary paediatric neuromuscular centre between 2002 and 2016 was performed. Data collected included age at and nature of presentation, path to diagnosis, genetic testing results, motor function, and occurrence of extramuscular features and complications. Results: Eighteen children (11 females, seven males; mean [SD] age at latest review 13y 10mo [3y 9mo], range 8–19y) from 16 families were identified. Age at onset of FSHD1 correlated with the size of deletion ( r =0.81) and most presentations were in children either younger than 5 years or older than 10 years. Children with onset before 5 years were more likely to present with non‐muscular symptoms and to develop extramuscular pathology, including developmental and psychiatric issues, hearing or visual impairments, and problems involving respiratory function and nutrition. No cases of epilepsy or cardiac arrhythmia were identified but two children died. Interpretation: The complexity and severity of FSHD1 presenting in early childhood underlines the importance of a multidisciplinary approach to the disorder. What this paper adds: Young children often present with non‐muscular pathology in facioscapulohumeral dystrophy type 1 (FSHD1), especially hearing loss. Age at onset in paediatric FSHD1 appears bimodal: under 5 years or in adolescence. Prolonged delays to diagnosis are common. Children with very early‐onset FSHD1 may require nutritional and/or respiratory support. Developmental and psychiatric comorbidities are common. What this paper adds: Young children often present with non‐muscular pathology in facioscapulohumeral dystrophy type 1 (FSHD1), especially hearing loss. Age at onset in paediatric FSHD1 appears bimodal: under 5 years or in adolescence. Prolonged delays to diagnosis are common. Children with very early‐onset FSHD1 may require nutritional and/or respiratory support. Developmental and psychiatric comorbidities are common. This article is commented on by Bernardino Gomes on page 865 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Características Clínicas de la distrofia fascioescapulohumeral 1 en la niñez: Objetivo: Explorar el curso clínico de los pacientes que presentan distrofina fascioescapulohumeral tipo 1 (FSHD1) en la niñez; con un enfoque que identifique las áreas que difieren de otros pacientes mayores; y, que tipo de soporte extra o monitorización podrían requerir. Método: Estudio retrospectivo de revisión de casos de niños con FSHD1, que fueron seguidos en un centro neuromuscular pediátrico terciario entre los años 2002 y 2016. La información recogida incluye edad y forma de presentación, algoritmo diagnóstico, resultados de los estudios genéticos, función motriz y aparición de síntomas extra‐musculares y complicaciones. Resultados: Dieciocho niños (11 niñas y siete varones; media [desviación standard] edad de la última revisión 13 años 10 meses [3 años 9 meses] rango 8–19 años) de 16 familias fueron identificados. La edad de aparición de del FSHD1 se correlacionó con el tamaño de la deleción ( r  = 0.81) y la mayor parte de los debuts fueron en niños menores de 5 años o mayores de 10. Aquellos niños cuyo inicio fue antes de los 5 años, mayormente se presentaban con síntomas no‐musculares y desarrollaron patología extra‐muscular que incluían afectación del desarrollo y psiquiátrica, pérdida auditiva o visual, y, problemas que concernían a la función respiratoria o la nutrición. No se detectaron casos de arritmia o epilepsia, sin embargo, dos niños fallecieron. Interpretación: La complejidad y severidad de la presentación de la FSHD1 en la infancia temprana, resalta la importancia de un abordaje multidisciplinar de esta condición de salud. Resumo: Aspectos clínicos da distrofia muscular facio‐escapulo‐umeral 1 na infância: Objetivo: Explorar o curso clínico de pacientes apresentando distrofia muscular facio‐escapulo‐tipo 1 (DFEU1) na infância, com vistas a identificar áreas em que eles diferem de pacientes mais velhos, e onde suporte ou monitoramento adicionais podem ser necessários. Método: Uma revisão retrospectiva de casos de crianças com DFEU1 atendidas em um centro pediátrico neuromuscular terciário entre 2002 e 2016 foi realizada. Os dados coletados incluíram idade e natureza da apresentação, caminho até o diagnóstico, resultados de testes genéticos, função motora, e ocorrência de aspectos extramusculares e complicações. Resultados: Dezoito crianças (11 do sexo feminino, sete do sexo masculino; média [desvio padrão] da idade na última visita 13a10m [3a 9m], variação 8–19a) de 16 famílias foram identificadas. A idade no início da DFEU1 correlacionou com o tamanho da deleção ( r  = 0, 81) e a maior parte das apresentações foram em crianças ou com menos de 5 anos ou com mais de 10 anos. Crianças com início antes de 5 anos tinham maior probabilidade de apresentar sintomas não‐musculares e de desenvolver patologia extra‐muscular, incluindo questões desenvolvimentais e psiquiátricas, deficiência auditiva ou visual, e problemas envolvendo função respiratória e nutrição. Nenhum caso de epilepsia ou arritmia cardiac foi identificado, mas duas crianças foram a óbito. Interpretação: A complexidade e severidade da DFEU1 com apresentação precoce na infância realça a importância de abordagem multidisciplinar para esta desordem.